Serum Uric Acid and Kidney Disease Measures Independently Predict Cardiovascular and Total Mortality: The Uric Acid Right for Heart Health (URRAH) Project - Elisa Russo; Francesca Viazzi; Roberto Pontremoli; Carlo M. Barbagallo; Michele Bombelli; Edoardo Casiglia; Arrigo F. G. Cicero; Massimo Cirillo; Pietro Cirillo; Giovambattista Desideri; Lanfranco D'Elia; Raffaella Dell'Oro; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Serum uric acid predicts the onset and progression of kidney disease, and the occurrence of cardiovascular and all-cause mortality. Nevertheless, it is unclear which is the appropriate definition of hyperuricemia in presence of chronic kidney disease (CKD). Our goal was to study the independent impact of uric acid and CKD on mortality.Methods: We retrospectively investigated 21,963 patients from the URRAH study database. Hyperuricemia was defined on the basis of outcome specific cut-offs separately identified by ROC curves according to eGFR strata. The primary endpoints were cardiovascular and all-cause mortality.Results: After a mean follow-up of 9.8 year, there were 1,582 (7.20%) cardiovascular events and 3,130 (14.25%) deaths for all causes. The incidence of cardiovascular and all-cause mortality increased in parallel with reduction of eGFR strata and with progressively higher uric acid quartiles. During 215,618 person-years of follow-up, the incidence rate for cardiovascular mortality, stratified based on eGFR (>90, between 60 and 90 and <60 ml/min) was significantly higher in patients with hyperuricemia and albuminuria (3.8, 22.1 and 19.1, respectively) as compared to those with only one risk factor or none (0.4, 2.8 and 3.1, respectively). Serum uric acid and eGFR significantly interact in determining cardiovascular and all-cause mortality. For each SUA increase of 1 mg/dl the risk for mortality increased by 10% even after adjustment for potential confounding factors included eGFR and the presence of albuminuria.Conclusions: hyperuricemia is a risk factor for cardiovascular and all-cause mortality additively to eGFR strata and albuminuria, in patients at cardiovascular risk.